When Catholics Attack. The Counter-Reformation in Fractured Regions of Europe (discussiedossier over Catholic Identity and the Revolt of the Netherlands, 1520-1635) - Questier, M. (BMGN - Low Countries Historical Review, 2011)
Pollmann, Judith, Catholic Identity and the Revolt of the Netherlands 1520-1635 (Past and Present; Oxford: Oxford University Press, 2011, xiv + 239 blz., ISBN 978 0 19 960991 8). This review looks at Judith Pollmann’s Catholic Identity and the Revolt of the Netherlands 1520-1635 in a number of contexts, but particularly the one supplied by the British Isles’ experience of the Reformation and the Counter-Reformation in the sixteenth and early seventeenth centuries. Following the line taken in Professor Pollmann’s account of the reaction against Calvinism in this period, it argues that if one wants to see what the sharp edges of the Counter-Reformation look like, then one should look at the regions of Europe which experienced conflict over faith. The Netherlands was one such area; the British Isles was another. The latter has more often than not been ignored by accounts of the European reaction to the Reformation. I want to suggest that it is of real relevance to put the two together and see what can be made of the similarities and differences between them. This review is part of the discussion forum 'Catholic Identity and the Revolt of the Netherlands 1520-1635' (Judith Pollmann).